Association of white matter hyperintensity with systemic inflammation markers and cognitive assessments: a cross-sectional study via SHAP analysis - Gao, Dewang; Lv, Jiayu; Li, Xinhui; Yong, Wen; Yu, Wenlong; Wang, Lu; Ma, Shangjia; Li, Hua; Zhang, Shuaiqiang; Guo, Zi; Yan, Hao; Ju, Zhipeng; et al. (Frontiers in Aging Neuroscience, 2025)
BackgroundWhite matter hyperintensity (WMH), a common neuroimaging feature in the older adults, has not been systematically elucidated regarding its association with cognitive function and systemic inflammation.AimTo develop and validate a clinical model for higher WMH burden integrating MoCA and CBC-derived inflammatory markers, and to quantify their independent and joint associations with WMH severity.MethodsThis study retrospectively collected data from patients with WMH at the First Affiliated Hospital of Baotou Medical College (December 2023–December 2024). We used univariate and multivariate logistic regression analyses to identify WMH-related variables. Then, we constructed an artificial neural network model and performed 10-fold cross-validation for internal validation and model performance comparison. The Shapley Additive Explanations (SHAP) method was employed to evaluate both models.ResultsCorrelation analysis revealed a significant association between the systemic inflammation response index (SIRI) and WMH burden (P< 0.01). Multivariate logistic regression analysis identified age, hypertension, high-density lipoprotein (HDL), previous cerebrovascular disease, the systemic inflammation response index (SIRI), and the Montreal Cognitive Assessment (MoCA) score as independent predictors of WMH burden. Ten-fold cross-validation showed that the set neural network model performed as well as the logistic regression model (AUC = 0.81). SHAP-based visual analysis identified age, MoCA score, and hypertension as key driving factors.ConclusionAge, hypertension, previous cerebrovascular disease, HDL, SIRI, and MoCA score are independent risk factors for moderate to severe WMH occurred. The model integrating MoCA and inflammatory markers accurately predicts moderate to Severe WMH. This study offers a multidimensional assessment framework for WMH risk stratification and early intervention.